A report on practice in industry training in fish processing technology. - Juliano, Myra L. (College of Fisheries, University of the Philippines, 1980)
In Philippines canning is practiced as a means of preserving fish and other fishery products. It involves the application of heat to food placed in a hermetically sealed container. Microorganisms and enzymes that cause spoilage of the canned product under normal conditions are killed and in activated, respectively.